2017
DOI: 10.1016/j.healun.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Donor-specific anti-HLA antibodies with antibody-mediated rejection and long-term outcomes following heart transplantation

Abstract: Introduction Donor specific anti-HLA antibodies (DSA) are common following heart transplantation and are associated with rejection, cardiac allograft vasculopathy (CAV), and mortality. Currently a non-invasive diagnostic test for pathologic AMR (pAMR) does not exist. Methods 221 consecutive adult patients underwent heart transplantation from January 1st, 2010 through August 31th, 2013 and followed through October 1st, 2015. The primary objective was to determine whether the presence of DSA could detect AMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 21 publications
5
93
0
2
Order By: Relevance
“…However, it is noteworthy that only a minority of patients cleared all DSA in spite of aggressive antibody-depleting therapy. Furthermore, the prevalence of DSA to class II HLA, and to HLA-DQ in particular, in our cohort is consistent with previous studies in pulmonary, renal, and cardiac AMR (2, 3, 5, 2833). Emerging data suggest that HLA-DQ may be uniquely immunogenic (34).…”
Section: Discussionsupporting
confidence: 92%
“…However, it is noteworthy that only a minority of patients cleared all DSA in spite of aggressive antibody-depleting therapy. Furthermore, the prevalence of DSA to class II HLA, and to HLA-DQ in particular, in our cohort is consistent with previous studies in pulmonary, renal, and cardiac AMR (2, 3, 5, 2833). Emerging data suggest that HLA-DQ may be uniquely immunogenic (34).…”
Section: Discussionsupporting
confidence: 92%
“…19,20 In an unselected contemporary heart transplant population, however, outcomes appear to have improved even in al- F I G U R E 4 Change in percent atheroma volume between baseline and month 12 in subjects who did not and who did meet the composite endpoint, the endpoint of death, and retransplantation and the endpoint of stent, myocardial infarction, or CAV diagnosis after 12 months seemed to be associated with less risk of CAV in the long-term in the CTOT-18 study. However, intermediate-term outcomes were similar in subjects with and without anti-HLA antibody.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, DSA and manifestations of AMR have been extensively investigated as measurable markers of the immune activation against vascular alloantigens. In our review, we found that eleven of twelve studies supported DSA/AMR involvement with CAV development [], with the only neutral study likely underpowered by the very small sample size. Anti‐HLA DSA class II and combination of class I and class II were found associated with angiographic CAV , while non‐DSA HLA antibodies did not appear to bear meaningful risk .…”
Section: Discussionmentioning
confidence: 99%